(untitled) (Journal of Pathology of Nepal, 2018)
Background: This study aims to establish correlation of ultrasonography guided fine needle aspiration cytology (USG-FNAC) of thyroid nodules with histology. USG-FNAC was carried out in fifty cases of thyroid nodules and the result of USG-FNAC was compared with histopathology. Materials and Methods: The study was performed in the Department of Pathology, National Academy of Medical Sciences, Bir Hospital over a period of one year. Fine needle aspiration of solid area of thyroid nodule was done in each case with USG guidance. FNAC results were classified according to Bethesda system of reporting. Finally, comparison was done between cytological and histological findings. Results: The age of patients that underwent thyroidectomy ranged from 16 - 70 years. Maximum number of cases fell in age group 31-40 years. Female patients outnumbered male patients by a ratio of 9: 1.On cytological study, 70% cases were diagnosed as benign, 28% as malignant and 2% as inadequate for evaluation. On histopathology, 70% cases of diagnosed cases were benign lesions. Nodular hyperplasia and colloid goiter were kept under the term ‘follicular nodule’. Follicular nodule was the most commonly diagnosed thyroid lesion. Fifteen cases of nodular hyperplasia and fourteen cases of colloid goiter were detected. Total number of malignant cases diagnosed was 15, out of which papillary carcinoma was the commonest (66.67%). We found two cases of medullary thyroid carcinoma. Conclusion: Sensitivity and specificity of USG-FNAC was 93.33 % and 100 %, respectively. The study showed significant correlation between FNAC (USG-guided in this study) and histopathology.